Applying healthcare failure mode and effect analysis to enhance patient-controlled analgesia in acute post anesthesia pain management - Chen, Shaoru; Zhang, Hongmei; Zhi, Hui; Wang, Jie (Frontiers in Medicine, 2025)
PurposeThis study aimed to evaluate the application of Healthcare Failure Mode and Effect Analysis (HFMEA) to optimize the patient-controlled analgesia management process for patients experiencing acute pain after general anesthesia.MethodsIn this retrospective study, the experimental group included 475 patients who underwent general anesthesia between July and December 2024, whereas the control group included 503 patients between January and June 2024. The experimental group received an HFMEA-optimized analgesia management process, whereas the control group received the standard nursing protocol. Patients’ pain scores, post-anesthesia care unit (PACU) stay length, and risk priority number (RPN) values were compared before and after HFMEA implementation.ResultsFollowing implementation, RPN values decreased from high to low risk, pain scores dropped significantly, and PACU stay was shortened (p < 0.05).ConclusionImplementation of an HFMEA-optimized analgesia process for patients with acute post-general anesthesia pain improves pain control and speeds recovery.